SCREENING THE ANTIBACTERIAL POTENTIAL OF Avicennia marina MANGROVE LEAF EXTRACT AS A NATURAL ANTIBIOTIC INGREDIENT - Sibarani, Michael Parluhutan Jupiter; Effendi, Irwan; Yoswaty, Dessy (Asian Journal of Aquatic Sciences, 2024)
Bacterial resistance to antibiotics is a global health problem caused by two factors, namely natural resistance and acquired resistance. Several factors can cause problems. The problem in this research is whether Avicennia marina mangrove leaf extract found in the mangrove ecosystem in Bandar Bakau, Pangkalan Sesai Village, Dumai City, can be used as an antibiotic. This research was conducted in January-March 2024. This research aimed to determine the potential of mangrove leaf extract A. marina as an antibiotic against pathogenic bacteria Vibrio sp, Aeromonas sp, and Pseudomonas sp. The results of this research will provide benefits in the form of information regarding the potential of A. marina mangrove leaf extract as an antibiotic. The methods used in this research are survey methods and experimental methods. The samples were then analyzed using the paper disk diffusion method at the Marine Microbiology Laboratory, Faculty of Fisheries and Marine Science, Universitas Riau. The data obtained is then presented and explained descriptively. The research results showed that antibiotics added to A. marina leaf extract could inhibit the growth of A.hydrophila bacteria based on the inhibition zone formed of 11mm. A.marina contains alkaloids, terpenoids, and flavonoids and has antibacterial properties against A.hydrophila bacteria. Based on the data, it can be concluded that A.marina leaf extract can be used against pathogenic bacteria